Identity and the learning process: ePortfolios and higher education Arts students - Bennett, Dawn (International Society for Music Education, 2014)
Graduate employability is a growing concern for higher education. Many Arts graduates need to shape their work to meet personal and professional needs, and successful negotiation of this type of career requires resilience, a strong sense of identity, and adequate preparation. This paper reports findings from a collaborative study undertaken at four Australian higher education institutions. The study involved students in classical and contemporary music, music education, music technology, and writing. In this paper we report the impact of electronic portfolios on learner identity, drawing our evidence from survey and focus group interview data. As the learning process rather than the technological tool drove the study, the findings can inform curriculum and practice across higher education creative and performing Arts.